The effect of standing posture on amplitude and variability of postural tremor in Parkinson's disease. (14th May 2023) - Morrison, S.; Reilly, N.; Schussler, E.; Kerr, G.
Highlights: Tremor is a common motor problem associated with older adults with Parkinson's disease. Impact of an individual's postural position (i.e. sitting vs standing) on their tremor was assessed. Consistency of tremor was assessed through intra-individual variability. For all persons, the tremor measured during standing was greater than when sitting. Increased postural demands related to standing may underlie the reported increases in tremor amplitude. Abstract: Introduction: This study examined whether altering body position (i.e., sitting or standing) affected the dynamics of physiological tremor for healthy older adults and persons with Parkinson's disease (PD). It was also of interest to determine how consistent the tremor was for both groups as determined by examining changes in within-subject variability of tremor amplitude, regularity and frequency. Methods: Ten Parkinsonian participants (65.1 ± 3.2 yrs.) and twelve elderly persons (71.2 ± 2.6 yrs.) participated in this study. Tremor was collected from the index finger and hand segments using lightweight accelerometers during the performance of a bilateral pointing task. Persons performed the pointing task in a standing or sitting position. Results: As expected, the tremor for the PD persons was greater in magnitude (mean RMS, peak power), more regular (lower SampEn), and more inconsistent from trial-to-trial (increased intra-individual variability, IIV) than the tremor recorded for the elderly. Further, when assessed during standing, the magnitude of the tremor for all individuals (elderly and PD) was greater, more variable, and less complex compared to the tremor when assessed during the sitting posture. The only measure which did not change within each group was the frequency of the major tremor peak which remained consistent, showing no significant change between limbs or as a function of the posture adopted. Conclusion: The findings revealed that tremor increased in amplitude and decreased in regularity for all individuals was assessed when standing compared to sitting. It is likely that these increases were task-related, reflecting the increased physical demands of performing the task when standing rather than being driven by specific age- or disease-related changes in the mechanisms underlying tremorgenesis. Further, the tremor for the PD individuals tended to be more variable from trial-by-trial in terms of both amplitude and regularity as compared to the elderly persons. Interestingly, the only tremor metric which showed no change within each group was the frequency of the major tremor peak which was consistent within both groups irrespective of the posture adopted.